2013
DOI: 10.3892/ol.2013.1175
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in thymidylate synthase and reduced folate carrier (SLC19A1) genes predict survival outcome in advanced non-small cell lung cancer patients treated with pemetrexed-based chemotherapy

Abstract: The aim of this study was to evaluate the association between thymidylate synthase (TS), methylenetetrahydrofolate reductase (MTHFR) and reduced folate carrier (SLC19A1) gene polymorphisms and the treatment efficacy of pemetrexed-based chemotherapy in advanced non-small cell lung cancer (NSCLC). Advanced NSCLC patients received pemetrexed and cisplatin every three weeks. Polymorphisms in the TS, MTHFR and SLC19A1 genes were detected in peripheral blood samples using DNA sequencing and Taqman PCR. An analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
(36 reference statements)
2
26
1
Order By: Relevance
“…Previous studies reported a 2.6-fold higher TS expression with 3 copies (TSER*3) of the R than with 2 copies (TSER*2) [42]. The variable number of repeats was associated with outcome after pemetrexed treatment in patients with different malignancies, including lung cancers [43,44]. However, these data were not always confirmed in other studies in NSCLC [45][46][47].…”
Section: Pharmacogenetics Of Pemetrexedcontrasting
confidence: 51%
See 3 more Smart Citations
“…Previous studies reported a 2.6-fold higher TS expression with 3 copies (TSER*3) of the R than with 2 copies (TSER*2) [42]. The variable number of repeats was associated with outcome after pemetrexed treatment in patients with different malignancies, including lung cancers [43,44]. However, these data were not always confirmed in other studies in NSCLC [45][46][47].…”
Section: Pharmacogenetics Of Pemetrexedcontrasting
confidence: 51%
“…In contrast, pharmacogenetic analyses in a randomized phase II trial aiming to optimize the administration schedule of pemetrexed and gemcitabine in 54 chemotherapy-naive patients with advanced NSCLC did not show any correlations with outcome for GGH IVS7(1478) and IVS2(1307) [49]. However, the latter trial supported the association of RFC-exon6-SNP with outcome following pemetrexed treatment [49], which was also reported in the recent research by Li and collaborators [44].…”
Section: Pharmacogenetics Of Pemetrexedmentioning
confidence: 36%
See 2 more Smart Citations
“…7,8 Furthermore, a number of polymorphic SLC19A1 variants have been shown to influence pemetrexed tolerability and survival after therapy (Table 1). [9][10][11] More recently, the proton-coupled folate transporter has been shown to possess high affinity for pemetrexed and has been confirmed as an important mechanism of cellular influx. 12,13 A third route of cellular uptake of uncertain significance, is mediated by folate receptors (FR) -a and -b, which are anchored to the cellular membrane, transporting folate derivatives via a complex endocytotic mechanism.…”
Section: Introductionmentioning
confidence: 98%